Centre of mass kinematics of fast bowling in cricket - Ferdinands, R.; Marshall, R. N.; Kersting, U. (Sports Biomechanics, 2010)
Kinematic studies have shown that fast bowlers have run-up velocities, based on centre of mass velocity calculations, which are comparable to elite javelin throwers. In this study, 34 fast bowlers (22.3 ± 3.7 years) of premier grade level and above were tested using a three-dimensional (3-D) motion analysis system (240 Hz). Bowlers were divided into four speed groups: slow-medium, medium, medium-fast, and fast. The mean centre of mass velocity at back foot contact (run-up speed) was 5.3 ± 0.6 m/s. Centre of mass velocity at back foot contact was significantly faster in the fastest two bowling groups compared to the slow-medium bowling group. In addition, stepwise multiple regression analysis showed that the centre of mass deceleration over the delivery stride phase was the strongest predictor of ball speed in the faster bowling groups. In conclusion, centre of mass kinematics are an important determinant of ball speed generation in fast bowlers. In particular, bowlers able to coordinate their bowling action with periods of centre of mass deceleration may be more likely to generate high ball speed.